Effects of Different Training Intensity Distribution in Recreational Runners - Festa, Luca; Tarperi, Cantor; Skroce, Kristina; La Torre, Antonio; Schena, Federico (Frontiers in Sports and Active Living, 2020)
Purpose: To compare the impact of two different training intensity distributions in terms of conditional and performance parameters and spent time to training in recreational athletes. Methods: Two different training intensity distribution model were performed for 8 weeks by 38 recreational runners. Runners recruited were randomly assigned to 2 different training models based on HR intensity detected with maximal test. The percentage distribution splitted in zone 1, 2 and 3 were by 77/3/20 and 40/50/10 in polarized endurance training group (PET) and focused endurance training (FOC) group respectively. Programs were balanced for total training impulse (TRIMP). To evaluate effects of training, before and after treatment were performed a maximal exercise test to determine Maximal Oxygen Uptake (V’O2max), Ventilatory Threshold (VT), respiratory-compensation point (RCT) Running Economy (RE) and 2 Km performance. To investigate the effects of training on muscular performance were performed one repetition maximum (1RM), squat jump (SJ) and counter movement jump (CMJ). Results: Both groups significantly improved their velocity at V’O2max (3.2% and 4.0%), at VT (4.0% and 3.2%), RCT (5.7% and 3.4%), the average velocity in 2 Km performance (3.5% and 3.0%) and RE (-5.3% and -8.7%) for PET and FOC respectively for each variable. No differences were found between the groups on any parameter investigated except about the total training time (PET = 29.8  3.1h and FOC = 24.8  2.0 h). Conclusion: Focused Endurance Training obtains similar improvements than Polarized Endurance Training saving 17% of training time in recreational runners.